Correlation Beetwen Body Fat Percent, Circle Ratio Waist Panel, Physical Activities with VO2Max Value on Employees of Aisyah Pringsewu University in 2021 - Ramadhana Komala; Alifiyanti Muharramah; Afiska Prima Dewi; Desti Ambar Wati; Wiwi Febriani (Universitas Aisyah Pringsewu, 2022)
VO2max is one way to measure cardiorespiratory fitness. One of the factors that cause heart disease is low cardiorespiratory fitness. The purpose of this study was to determine the relationship between percent body fat, waist-to-hip ratio, physical activity with the value of VO2max in Aisyah Pringsewu University Employees in 2021. The design of this study used a cross-sectional. The number of research samples was 78 consisting of 30 men and 48 women with an average age of 30.81 ± 6.58 years. Fitness was measured using the 20-Meters Shuttle Run Test. The results of statistical analysis showed that there was a significant relationship between percent body fat and VO2max value (p less than 0.05), physical activity with VO2max value (p less than 0.05) and there was no relationship between waist-to-hip ratio and VO2max value (p less than 0.05). 0.05. The conclusion is good, percent body fat, and physical activity have a significant relationship with the vo2max value in employees, but the ratio of waist and hip circumference has no significant relationship. Abstrack: VO2max adalah salah satu cara untuk mengukur kebugaran kardiorespirasi. Salah satu faktor penyebab terjadinya penyakit jantung yaitu rendahnya kebugaran kardiorespiratori. Tujuan penelitian ini adalah untuk mengetetahui hubungan persen lemak tubuh, rasio lingkar pinggang panggul, aktivitas fisikdengan nilai VO2max pada Karyawan Universitas Aisyah Pringsewu Tahun 2021. Desain penelitian ini menggunakanCross Sectional. Jumlah sampel penelitian sebesar78yang terdiri dari 30 laki laki dan 48 perempuan dengan usia rata rata 30,81 ± 6,58 tahun. Kebugaran diukur menggunakan 20-Meters Shuttle Run Test. Hasil analisis statistik menunjukkanterdapat hubungan yang signifikan antarapersen lemak tubuh dengan nilai VO2max (p kurang dari 0,05), aktivitas fisik dengan nilai VO2max (p kurang dari 0,05) serta tidak ada hubungan antara rasio lingkar pinggang panggul dengan nilai VO2max (p kurang dari 0,05). Kesimpulannya baik, persen lemak tubuh, dan aktivitas fisik memiliki hubungan yang bermakna dengan nilai vo2max pada karyawan. Tetapi, rasio lingkar pinggang dan panggul tidak terdapat hubungan yang signifikan.